1980
DOI: 10.21273/jashs.105.6.858
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol Induced Water Stress Effect on Apple Seedlings. II. 45Calcium Uptake1

Abstract: Polyethylene glycol (PEG)-induced water stress in nutrient solutions decreased both water consumption and 45Ca uptake by apple seedlings (Malus domestica Borkh.) The decrease in water uptake was more severe than the decrease in 45Ca uptake. When 45Ca uptake was calculated on the basis of water consumption, it was found that 45Ca uptake was not dependent on water uptake although water was necessary for movement of 45Ca. In split-root experiments, PEG and 45Ca were either applied to the same half of the root or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…1). Similar responses to PEG-induced water stress at -1.0 bar were observed in previous studies (4,16). There was also a significant K-pretreatment x PEG x day interaction on apple seedlings' water consumption rate (Table 3).…”
Section: R Esults and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…1). Similar responses to PEG-induced water stress at -1.0 bar were observed in previous studies (4,16). There was also a significant K-pretreatment x PEG x day interaction on apple seedlings' water consumption rate (Table 3).…”
Section: R Esults and Discussionsupporting
confidence: 85%
“…The apple seedlings used in that experiment can be considered here as high-K plants. The above data indicate that PEG-induced water stress decreased the ab sorption capacity of the roots (4,16,17,18), and this effect can be noted in as short a period of time as 2 weeks. Clark (2) reported that an osmotic water stress ( -1 .0 bar) decreased N, P, and Rb concentrations in wheat within 24 hr.…”
Section: R Esults and Discussionmentioning
confidence: 62%
“…An 11-mm-diameter circle was cut with a cork borer from the youngest fully expanded leaf of each plant. The radioactivity of the fresh stem and leaf sections was determined by counting in a Nuclear-Chicago planchet counter according to procedures described previously (7). This counting method was acceptable, despite the self-absorption of some ra dioactivity by the sample tissue, because equal amounts of tissue were used and only relative radioactivity of the samples was needed.…”
Section: Methodsmentioning
confidence: 99%
“…Mason (12) found that seedlings of apple grown in soil which was allowed to dry until the plants wilted had much less total Ca than seedlings grown at field capacity. Uptake of 45Ca by apple seedlings in nutrient solution was reduced when solution osmotic potential was lowered (7).…”
mentioning
confidence: 97%
“…One group was used as control, with poplars grown in a normal nutrient solution (1/2 Hoagland), whereas the other group was treated with a nutrient solution (1/2 Hoagland) containing 20% PEG6000 for 7 days. Physiological and biochemical indexes of three mature leaves at the same position were analyzed, and total RNA was extracted from the fifth leaf at the top of each poplar (Gergely et al, 1980). The lower epidermis of leaves under osmotic stress and control treatments was peeled off with scotch tape, then photographed under an optical microscope to measure the ratio of stomatal length and width (Gao et al, 2020).…”
Section: Osmotic Stress Tolerance Assaymentioning
confidence: 99%